Activation of Piezo1 and TRPV4 channels contributes to hCMEC/D3 cell mechano-sensing - An, Wenhan; Sun, Min; Zhang, Xiulin; Huang, Laigang; Liu, Hanwen; Cui, Baojuan (Frontiers in Physiology, 2025)
IntroductionTRPV4 and Piezo1 channels have been considered two important mechanical sensors. To examine the role of these two channels in blood brain barrier (BBB) mechano-sensing, the expression and function of TRPV4 and PIEZO1 in hCMEC/D3, an in vitro model for human BBB endothelial cells, were investigated.MethodsTRPV4 and PIEZO1 mRNA and protein expression were analysed by RT-PCR, immunofluorescence and western blot, respectively, while their mechano-sensing function was investigated by calcium imaging.ResultsAmong the four mechano-sensing channels examined (TRPV2, TRPV4, PIEZO1 and Piezo2), TRPV4 and PIEZO1 were the two most abundantly expressed in hCMEC/D3 cells at the mRNA level. TRPV4 and PIEZO1 proteins were detected by immunofluorescence, western blot. The calcium imaging using channel-specific agonists/antagonists provided evidence of their function. Mechanical stimuli (poke or flow shear stress) induced a prominent increase in intracellular Ca2+([Ca2+]i) in hCMEC/D3 cells, which was significantly inhibited by application of selective TRPV4 or Piezo1 antagonists. Activation of PIEZO1 and TRPV4 using selective agonists resulted in the release of adenosine triphosphate (ATP) but not nitric oxide (NO). Extracellular ATP hydrolysis with apyrase, or blocking of P2X and P2Y purinoceptors with PPADS, significantly reduced mechanical stimulus-induced increases in [Ca2+]i in both the stimulated cell and neighboring cells.